Software package for personal finance - Chew, Jun Qiao. (2013)
This report discusses the design and development of a software package to help simplify the process of tracking one’s personal finance and investment portfolio. This report also discusses the two main functions of the software. One of this function was named as Cash Flow Manager. It manages the spending, income and saving of individuals. The other function is called Portfolio Manager that manages the stocks, bonds and properties portfolio investments. Both functions allows users to record, edit, remove and search for the respective personal income, expense, saving and investments. This software also uses an intuitive Graphical User Interface with aims to make it user friendly. To ensure the usability of this software, this report will cover the various test that were conducted to ensure this software is able to execute its functions and handle invalid or unique inputs entered by users.